2019
DOI: 10.3892/ijmm.2019.4166
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene restores the effect of ischemic postconditioning on myocardial ischemia‑reperfusion injury in hypercholesterolemic rats

Abstract: Ischemic postconditioning (IPoC) has been demonstrated to prevent myocardial ischemia-reperfusion injury (MIRI), but its cardioprotective effect is abrogated by hypercholesterolemia. The aim of the present study was to determine whether lycopene (LP), a type of carotenoid, can restore the cardioprotective effect of IPoC in hypercholesterolemic rats. Male Wistar rats were fed a cholesterol-enriched diet for 12 weeks to establish a hypercholesterolemic model. The rat hearts were isolated and subjected to 30 min … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…(1) APPL1 was involved in myocardial injury induced by hypoxia/reperfusion. (2) The inflammation and apoptosis caused by hypoxia/reperfusion could be regulated through APPL1 via APAF-1/Caspase9 signaling pathway. (3) APPL1 affected the binding of APAF-1 and Caspase9.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) APPL1 was involved in myocardial injury induced by hypoxia/reperfusion. (2) The inflammation and apoptosis caused by hypoxia/reperfusion could be regulated through APPL1 via APAF-1/Caspase9 signaling pathway. (3) APPL1 affected the binding of APAF-1 and Caspase9.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Myocardial ischemia is a severe pathological condition that mediates the progression of multiple cardiovascular diseases, including myocardial infarction, stroke, and peripheral vascular disease [1]. An early intervention to restore blood flow to the ischemic myocardium is a common strategy to salvage cardiomyocytes and limit infarct size [2,3]. However, after interruption of myocardial blood supply and oxygen supply in a short time, the reperfusion often results in paradoxical cardiomyocyte death and dysfunction, a phenomenon termed myocardial ischemia/hypoxia-reperfusion injury [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Further, some studies showed that high cholesterol not only exacerbated myocardial damage but also affected the therapeutic effects of PostC [108][109][110][111][112]. The combination of PostC and a certain dose of lycopene could significantly improve severe myocardial I/R injuries in patients with high cholesterol [113], justifying further exploration of potential combination therapies in myocardial I/R injuries under other conditions (e.g., diabetes and hyperlipidemia [114,115]). Oxidative Medicine and Cellular Longevity Furthermore, one study found that the cardioprotective effects of IP and PostC were activated through the posttranslational modification of proteins (S-nitrosylation, SNO) mediated by RISK and SAFE [116].…”
Section: The Effects Of Lycopene On Ischemic and I/r Injuriesmentioning
confidence: 99%
“…Oxidative Medicine and Cellular Longevity Furthermore, one study found that the cardioprotective effects of IP and PostC were activated through the posttranslational modification of proteins (S-nitrosylation, SNO) mediated by RISK and SAFE [116]. Most of the evidence suggests that as an adjunctive therapeutic measure, lycopene acts on many downstream signal molecules of RISK and SAFE (e.g., activating ERK, Akt and PI3K and inhibiting STAT3 and p-GSK-3β) to attenuate myocardial I/R injury [113]. These studies implied that lycopene seemed to promote SNO.…”
Section: The Effects Of Lycopene On Ischemic and I/r Injuriesmentioning
confidence: 99%
“…Herein, we compiled the most recent findings regarding the biological and pharmacological activities of lycopene (Table 1 (Tab. 1) ; References in Table 1: Albrahim and Alonazi, 2021[ 2 ]; Arakeri et al, 2020[ 3 ]; Asgary et al, 2021[ 5 ]; Babaei et al, 2021[ 6 ]; Bedir et al, 2021[ 7 ]; Cao et al, 2021[ 8 ]; Celik et al, 2020[ 9 ]; Chen et al, 2019[ 10 ], 2021[ 11 ]; Cheng et al, 2020[ 12 ]; Choi and Kim, 2020[ 15 ]; Choi et al, 2021[ 14 ]; de Barros Elias et al, 2019[ 17 ]; Dobrzyńska and Gajowik, 2020[ 18 ]; Dobrzyńska et al, 2019[ 19 ]; Duan et al, 2019[ 20 ]; Eita et al, 2021[ 21 ]; El Morsy and Ahmed, 2020[ 22 ]; Elgawish et al, 2020[ 23 ]; Eze et al, 2019[ 24 ]; Fachinello et al, 2020[ 25 ]; Fallah et al, 2021[ 26 ]; Fan et al, 2019[ 27 ]; Farouk et al, 2021[ 28 ]; Fu et al, 2020[ 29 ]; Gao et al, 2019[ 30 ]; Greish et al, 2021[ 32 ]; Hashimoto et al, 2020[ 33 ]; Huang et al, 2019[ 34 ]; İkiz et al, 2021[ 35 ]; Jesuz et al, 2019[ 38 ]; Kang et al, 2021[ 40 ]; Kim et al, 2019[ 41 ]; Lee et al, 2021[ 42 ]; Leh et al, 2021[ 43 ]; Li et al, 2021[ 44 ]; Liu et al, 2021[ 45 ][ 46 ]; Ma et al, 2019[ 47 ]; Malekiyan et al, 2019[ 48 ]; Motallebnejad et al, 2020[ 50 ]; Mustra Rakic et al, 2021; Ni et al, 2020[ 51 ]; Ning et al, 2021[ 52 ]; Ou et al, 2020[ 53 ]; Park et al, 2020[ 54 ]; Polat et al, 2021[ 55 ]; Rajput et al, 2021[ 57 ]; Rasheed et al, 2020[ 59 ]; Residiwati et al, 2021[ 60 ]; Rocha et al, 2021[ 61 ]; Róvero Costa et al, 2019[ 62 ]; Sarker et al, 2021[ 63 ]; Soares et al, 2019[ 66 <...>…”
mentioning
confidence: 99%